2006
DOI: 10.1111/j.1574-6968.2006.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR detection ofSalmonellaspp. using primers targeting the quorum sensing genesdiA

Abstract: Bacteria communicate with one another and with their host using chemical signalling molecules. This phenomenon is generally described as quorum sensing. A set of primers for PCR detection of Salmonella spp. has been designed using as target the sdiA gene which encodes a signal receptor of the LuxR family. The PCR product (274 bp) was confirmed by sequencing. A number of 81 non-Salmonella strains (representing 24 different species) were tested and gave negative results, while a total of 101 different serotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 27 publications
4
30
0
2
Order By: Relevance
“…Notably, all the isolates demonstrated positive results on the sdiA gene amplification. sdiA is a quorum sensing gene that encodes a signal receptor of the LuxR family to achieve intercellular signaling for intestinal survival or colonization (Halatsi et al 2006;Walters and Sperandio 2006). Results of 100% prevalence for sdiA and hilA are consistent with the previous findings by Halatsi et al (2006) and Pathmanathan et al (2003) respectively, who reported that sdiA and hilA appeared to be conserved in S. enterica.…”
Section: Wandsworth Wa 1(m) Wa 2(m) Wa 3 (M)supporting
confidence: 84%
“…Notably, all the isolates demonstrated positive results on the sdiA gene amplification. sdiA is a quorum sensing gene that encodes a signal receptor of the LuxR family to achieve intercellular signaling for intestinal survival or colonization (Halatsi et al 2006;Walters and Sperandio 2006). Results of 100% prevalence for sdiA and hilA are consistent with the previous findings by Halatsi et al (2006) and Pathmanathan et al (2003) respectively, who reported that sdiA and hilA appeared to be conserved in S. enterica.…”
Section: Wandsworth Wa 1(m) Wa 2(m) Wa 3 (M)supporting
confidence: 84%
“…PCR amplification was performed using primer pairs described by Bhatta et al (2007), and primer pair sdiA1 and sdiA2 described by Halatsi et al (2006). The amplicon sizes of invA, spvC, and sdiA were 244 bp, 571 bp, and 274 bp, respectively.…”
Section: Detection Of Virulence and Quorum Sensing Genesmentioning
confidence: 99%
“…Primers sdiA1 and sdiA2 (Table 2) were used for Salmonella quorum sensing detection. Amplification was performed in a 25 µl final volume with a reaction mixture containing 0.125 µM of each sdiA primers (Halatsi et al, 2006).…”
Section: Its 16s-23s Pcr and Eric-pcrmentioning
confidence: 99%
“…These biofilms enable Salmonella to survive and spread in the environment outside the host (Janssens et al, 2008). Both biofilm production and pathogenicity are controlled and regulated by so-called quorum sensing (QS) systems (Halatsi et al, 2006;Williams, 2006). It has been reported that Salmonella SdiA detects and responds to AHL signals generated only by other microbial species (Sperandio, 2006;Walters and Sperandio, 2006).…”
mentioning
confidence: 99%